As days grow darker - Masterstroke; Bergbacka, Heidi; Juutinen, Janne; Kekoni, Markus; Kolehmainen, Marko (basisti); Kulomaa, Jussi; Nygård, Rainer; Rauhala, Niko; Salmela, Tommi (Dynamic Arts Records, 2009)
11 kappaletta.